Kualitas Pelayanan Pemasangan Listrik Prabayar Pada PT. PLN (Persero) Area Pelayanan Banyumanik Semarang - Dini Setyorini (Universitas Bina Sarana Informatika, 2019)
Abstract – It cannot be denied that at present the public service is a concern of the public. Ordinary public service come from agencies that serve the community for the needs of every community. This study aims to determine quality of service for prepaid electricity installation at PT. PLN (Persero) Banyumanik Semarang service area. Analysis of the data used is a score interpretation (IS) obtained from respondents. Respondents numbered 80 people using purposive sampling. While to complete this research, the author also uses secondary data obtained from various existing sources. Based on the results of the research conducted it can be concluded that the dimensions that show service quality include tangibles ( direct evidence), reliability, responsiveness, assurance and emphaty show a strong interpretation where customers feel satisfied with the quality service of PT. PLN (Persero) Banyumanik Semarang service area.Key words : quality, service, satisfaction